Comparative study of L/D lactic acid production in cultures of probiotic strains supplemented with carbohydrates from agave and other agroindustrial resources - Morales-Landa, Juan Luis; Lazcano-Díaz, Estefania; Escamilla-García, Erandi; Pérez-De la Rosa, Alan Gael; Luiz-Santos, Noé (Frontiers in Sustainable Food Systems, 2025)
The growth behavior and lactic acid production capacity including both L-lactic and D-lactic acid isomers of five probiotic strains (Lactobacillus plantarum ATCC® 8014, L. rhamnosus ATCC® 53103, L. casei ATCC® 334, L. reuteri ATCC® 55730, and Bifidobacterium animalis ENCB-IPN) were systematically evaluated using defined carbon sources. Each strain was cultured for 24 h in modified MRS broth, where glucose was replaced with 1% (10 g/L) of individual substrates: monosaccharides (fructose, glycerol, rhamnose, arabinose, mannose, xylose, galactose), disaccharides (sucrose, cellobiose, lactose), a trisaccharide (raffinose), agave-derived fructooligosaccharides (FOS), and high-molecular-weight agave fructans (FAPM, DP > 10). Bacterial growth was monitored via optical density (OD595), and the specific growth rate (μ) and maximum OD were calculated. Fructose supported the highest total lactic acid production, particularly in L. plantarum and B. animalis, followed by sucrose, mannose, and cellobiose. Notably, L. rhamnosus achieved the highest L-lactic acid proportion (96%) with FAPM, while L. casei yielded 92.5% with cellobiose. In contrast, the highest D-lactic acid proportions were obtained with lactose (71.35% in L. plantarum, 55.88% in L. reuteri) and with glycerol in L. casei (62%). Principal component analysis (PCA) showed limited correlation between growth and acid production when monosaccharides were used, but strong positive correlations were found with disaccharides and FOS, particularly between μ and lactic acid yield. This study highlights the relevance of using defined carbon sources to elucidate the substrate-specific metabolic behavior of probiotic strains. The results provide a comparative framework for selecting or engineering strains for targeted lactic acid production (including optical purity) and lay the foundation for future bioprocess optimization using complex substrates such as agro-industrial residues or functional oligosaccharides.